2023
DOI: 10.1007/s12649-022-02017-z
|View full text |Cite
|
Sign up to set email alerts
|

Sepedonium sp. and Phellinus sp. Novel Isolates: Growth Pattern and Production of Polysaccharide-Protein Complexes on Conventional and Grape Pomace Substrates

Abstract: Purpose The growth behavior of novel fungal isolates along with the production of bioactive compounds from mycelia mass during submerged fermentations were investigated using conventional synthetic media and agro-industrial residues as fermentation substrates. Methods Four novel isolated fungi, belonging to edible or medicinal species, were evaluated for their ex-situ growth on potato dextrose agar. Specific attention was designated to Sepedonium sp. and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…In our previous studies, GPE extract was evaluated as a substrate for the cultivation of Phellinus sp., Sepedonium sp. and Ganoderma lucidum strains [13,31]. A strain specificity was shown since, depending on the strain, biomass production increased or decreased compared with the synthetic media.…”
Section: Assessment Of Grape Pomace Extract (Gpe) As Fermentation Sub...mentioning
confidence: 96%
See 1 more Smart Citation
“…In our previous studies, GPE extract was evaluated as a substrate for the cultivation of Phellinus sp., Sepedonium sp. and Ganoderma lucidum strains [13,31]. A strain specificity was shown since, depending on the strain, biomass production increased or decreased compared with the synthetic media.…”
Section: Assessment Of Grape Pomace Extract (Gpe) As Fermentation Sub...mentioning
confidence: 96%
“…A previously described method was used to formulate grape pomace extract (GPE) using an aqueous extraction process. Briefly, the extraction of soluble, free sugars from grape pomace was performed at 40 • C for 2 h at a solid-to-liquid ratio of 1:10 (w/v) with deionized water [13]. The GPE contained ~5-6 g/L of glucose and ~5-6 g/L of fructose along with trace amounts of sucrose (0.4-0.5 g/L).…”
Section: Fermentation Supplements and Submerged Fermentations (Smfs)mentioning
confidence: 99%
“…and Sepedonium sp. isolates, TDW exhibited a decrease compared with glucose; however, that study implemented only static conditions [31]. In another study, Wei et al suggested that using an optimized ratio of glucose and sucrose improved the fungal mass of G. lucidum, along with polysaccharide and ganoderic acid production [26].…”
Section: Growth Behavior On Grape Pomace Extract (Gpe) As Nutrient Su...mentioning
confidence: 97%
“…Subsequent steps employed replacing commercial media with a feedstock derived from renewable resources, following the results obtained from conventional carbon sources. A preliminary characterization of GPE was performed in our previous study [31], where the low concentration of total phenolic content and free amino nitrogen (FAN) was also reported. The experiments initiated by applying GPE as the sole substrate in static and shaking conditions, and the fermentation kinetics are shown in Figure 1.…”
Section: Growth Behavior On Grape Pomace Extract (Gpe) As Nutrient Su...mentioning
confidence: 99%
See 1 more Smart Citation